1999
DOI: 10.1093/emboj/18.2.490
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Arabidopsis thaliana ribosomal protein S27 in mRNA degradation triggered by genotoxic stress

Abstract: A recessive Arabidopsis mutant with elevated sensitivity to DNA damaging treatments was identified in one out of 800 families generated by T-DNA insertion mutagenesis. The T-DNA generated a chromosomal deletion of 1287 bp in the promoter of one of three S27 ribosomal protein genes (ARS27A) preventing its expression. Seedlings of ars27A developed normally under standard growth conditions, suggesting wildtype proficiency of translation. However, growth was strongly inhibited in media supplemented with methyl met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 54 publications
3
87
0
Order By: Relevance
“…The crystal structure of the yeast small subunit showed that the sulfur atom of Cys-39 is displaced from a tetrahedral position of a four-cysteine zinc cluster presumably due to its methylation (23). This cluster is similar to that seen in bacterial DNA repair enzymes that demethylate spontaneously alkylated DNA, leading to the hypothesis that Rps27a may also be involved in DNA repair and/or resistance to alkylating agents (92,93). Here, the methylated protein may simply represent a dead end product of the repair reaction.…”
Section: Cysteine S-methylationmentioning
confidence: 84%
“…The crystal structure of the yeast small subunit showed that the sulfur atom of Cys-39 is displaced from a tetrahedral position of a four-cysteine zinc cluster presumably due to its methylation (23). This cluster is similar to that seen in bacterial DNA repair enzymes that demethylate spontaneously alkylated DNA, leading to the hypothesis that Rps27a may also be involved in DNA repair and/or resistance to alkylating agents (92,93). Here, the methylated protein may simply represent a dead end product of the repair reaction.…”
Section: Cysteine S-methylationmentioning
confidence: 84%
“…Specific roles for a ribosomal protein under stress situations have previously been observed in Arabidopsis. Arabidopsis rps27 mutant plants are normal under standard conditions but show elevated sensitivity to genotoxic stress and UV irradiation by their inability for the elimination of damaged transcripts (Revenkova et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of ARS27A gene expression in Arabidopsis thaliana leads to hypersensitivity to methyl methanesulfate treatment that is accompanied by inhibition of seedling growth and formation of tumor-like structures instead of auxiliary roots. The ARS27A protein is not required for translation; instead it is needed for the degradation of damaged mRNA in response to UV (56). It is possible that the RPS27L gene could play a similar role in humans.…”
Section: Discussionmentioning
confidence: 99%